Mitigation of environment impact of mycotoxins produced by Fusarium species - Bíró, Györgyi; Tamás, János; Borbély, János; Mézes, Lili; Hunyadi, Gergely (Acta Agraria Debreceniensis, 2012)
The Fusarium fungi hazards the grain quality of cereals, therefore significantly affects their utilization as animal feed or consumable product. The Fusarium can decrease the quality of wheat in different ways: decreases the germination capability, causes visible discoloration, mould may appear, reduces the dry material and nutrient content of the grain, causes mycotoxin infection – as a result given by its by-product. Micotoxins produced by Fusarium genus, as the trichotecenes (T-2, HT-2, deoxynivalenol, nivalenol, diacetoxyscirpenol, Fusarenone-X) and the zearalenone (F-2) are the most common in Hungary. Occurrence of fumonisins first discovered in 1988 are must be identified carefully. About 20–30% of the overall worldwide production of cereals is infected with Fusarium and its toxins, which situation is similar in Hungary. This infection causes serious yield-losses in cereal production. In the case of cereal products, which non-utilizable as forage seems, an optimal solution is utilizing as biogas raw material, but it is also important to examine the effect of the infected cereal on the anaerobe digestion process.